Asymmetric news responses of high‐frequency and non‐high‐frequency traders. Issue 3 (22nd April 2019) - Zhang, S. Sarah
Abstract: Using NASDAQ trade and Reuters news data, I show that the response of aggressive non‐high‐frequency traders (nHFTs) to news is stronger than that of aggressive high‐frequency traders (HFTs). Classifying news into quantitative ("hard") and less quantitative ("softer") news, the trading response of aggressive nHFTs to softer news exceeds HFTs' response. Positive news elicits greater return and nHFT responses than negative news during the 2008 financial crisis period. As this phenomenon persists even after excluding the 2008 short‐sale ban, the results support the hypothesis of nHFTs exhibiting stronger asymmetric responses during crisis periods.